Security Improvement on Biometric Based Authentication Scheme for Wireless Sensor Networks Using Fuzzy Extraction - Younsung Choi; Youngsook Lee; Dongho Won (International Journal of Distributed Sensor Networks)
Wireless sensor networks are used to monitor physical or environmental conditions. However, authenticating a user or sensor in wireless sensor networks is more difficult than in traditional networks owing to sensor network characteristics such as unreliable communication networks, resource limitation, and unattended operation. As a result, various authentication schemes have been proposed to provide secure and efficient communication. He et al. suggested a robust biometrics-based user authentication scheme, but Yoon and Kim indicated that their scheme had several security vulnerabilities. The latter then proposed an advanced biometrics-based user authentication scheme; in this paper, we analyze this advanced scheme and perform a cryptanalysis. Our analysis shows that Yoon and Kim's scheme has various security weaknesses such as a biometric recognition error, a user verification problem, lack of anonymity and perfect forward secrecy, session key exposure by the gateway node, vulnerability to denial of service attacks, and a revocation problem. Therefore, we suggest countermeasures that can be implemented to solve these problems and then propose a security-enhanced biometrics-based user authentication scheme using fuzzy extraction that conforms to the proposed countermeasures. Finally, we conduct a security analysis for the proposed biometrics-based user authentication scheme.